THE WEIGHT OF CARCASS AND GIBLET OF BROILER WITH COMMERCIAL AND FERMENTATION FEED SUBTITUTION - Nurlia, Sitti; Hafid, Harapin; Malesi, La (Indonesian Journal Of Animal Agricultural Science (IJAAS), 2020)
Utilization of agricultural and fishery waste in the form of rice bran, fish meal, and sago pulp is still underused because of its low nutrient content so that with quite simple processing technology, such as fermentation treatment using rumen liquid, this is a solution to increase the nutrient content of the feed ingredients. The substitution of the commercial ration with fermented ration is expected to increase the carcass weight and weight of broiler chicken giblets. This study aims to determine the carcass weight and weight of broiler chicken giblets which are given commercial ration fermentation rations. A total of 100 broiler chickens were kept in 20 cages with five treatments and four repetitions, each plot filled with 5 experimental chickens. The combination of treatment rations are R0 (control ration), R1 (control ration + 10% ration fermentation), R2 (control ration + 20% ration fermentation), R3 (ration control + 30% fermentation ration), R4 (ration control + 40% ration) fermentation ration). The parameters observed were carcass weight and giblet weight (gizzard, liver, and heart). The data obtained were compiled and analyzed for a variance with the F. test. If significantly different, further tests were performed using Duncan's Multiple Range Test. The results showed that the substitution of commercial rations with fermented ration had no significant effect (p> 0.05) on carcass weight and had a very significant effect (p <0.05) on liver weight, but had no significant effect (p> 0.05) on heart weight and gizzard. The level of use of 10% substitution of commercial rations with fermented ration was able to increase the weight of broiler chicken carcasses, while the weight of gizzard and heart increased at a level of 20%, while the use of commercial ration substitution with fermented ration 40% of liver weight decreased.